Microstructure and properties of a high temperature Al–Ce–Mn alloy produced by additive manufacturing. (1st September 2020) - Plotkowski, A.; Sisco, K.; Bahl, S.; Shyam, A.; Yang, Y.; Allard, L.; Nandwana, P.; Rossy, A. Marquez; Dehoff, R.R.
Abstract: An Al–10Ce-8Mn (wt%) alloy was designed and fabricated by laser powder bed fusion additive manufacturing (AM). The rapid cooling rates of the AM process produced a refined microstructure with a large fraction of reinforcing intermetallic phases. The tensile properties of the alloy were characterized in the as-fabricated state and following thermal exposure. The properties of the as-fabricated microstructure showed exceptional high-temperature performance and strength retention at elevated temperatures up to 400 °C relative to benchmark wrought Al and AM Al alloy properties. Characterization of the microstructure and thermodynamic modeling of the ternary Al–Ce–Mn system rationalized the solidification and solid-state phase transformations. Analysis of the relevant strengthening mechanisms for both the as-fabricated and thermally exposed conditions was performed. Graphical abstract: Image, graphical abstract